Medication safety in children : What role do dosing and formulations play? - Neubert, Antje; Rascher, Wolfgang (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2018)
Medication errors are more common in children compared to adults due to often missing efficacy evidence and limited or missing regulatory approvals for paediatric drugs.Roots of errors are located at different levels. They result, for example, from missing clinical studies that particularly investigate efficacy and correct dosing in younger age groups, the lack of age-appropriate dosage forms, the use of harmful ingredients, as well as the complicated and high-risk prescribing process.Electronic systems may improve the quality of drug prescriptions and reduce medication errors. The basic assumption is valid, evidence-based data behind such a system. In contrast to other countries, such a database is not yet available in Germany. The Plan of Action for the improvement of medication safety in Germany 2016-2019 (Aktionsplan) contains an action point "Creation of a database for dosing of paediatric medicines". Initial funding for 2 years has been granted for its implementation.Through systematic literature searches and the availability and provision of up-to-date knowledge on paediatric medicines, medication safety for children and adolescents can be improved. A database with relevant information to support more correct prescriptions within the paediatric population appears productive. The Aktionsplan has paved the way for the dissemination of evidence-based drug information for the country's paediatric population.
EVALuna2:35727